Impact of telenurse-led intervention in clinical trials on health literacy, empowerment, and health outcomes in patients with solid tumours: a pilot quasi-experimental study - Sergio Muñoz-Villaverde; María Martínez-García; Leticia Serrano-Oviedo; Francisco Javier Gómez-Romero; Ana María Sobrado-Sobrado; María Ángeles Cidoncha-Moreno; Juan Riesgo-Martín; Guillermo Pedreira-Robles; Paloma Garcimartin (BMC, 2024)
Abstract Background During the COVID-19 pandemic, decentralised clinical trials incorporated self-monitoring, self-reporting, and telenursing tools to address health literacy and health empowerment of patients enrolled in clinical trials. We aimed to determine the impact of an educational intervention using telenursing consultations on health literacy, health empowerment, and health-related quality of life in cancer patients enrolled in clinical trials by measuring the level of satisfaction with the care received and assessing the views of healthcare professionals concerning the advanced practice nurse (APN) role in oncology clinical trials. Methods In this pilot analytical, descriptive, longitudinal, quasi-experimental, and pre-post test study, an educational intervention was conducted by 5 visits with an APN using synchronous teleconsultation in patients starting cancer treatment for the first time in a clinical trial (n = 60), and health professionals working with the APN (n = 31). A descriptive analysis of the samples and questionnaires were utilised along with statistical comparisons. Results After the intervention, patients' health literacy (31.7%), health empowerment (18.3%), and health-related quality of life (33.3%) increased (p < 0.05), with a decrease and trend towards resolution of care needs (p < 0.05). Satisfaction with the quality and care received in terms of perceived convenience, transition, and continuity of care showed positive results in 64.9 ± 20.7, 77.6 ± 19.5, and 72.1 ± 20.4 of respondents, respectively. On the overall assessment of the APN role, healthcare professionals expressed a high level of agreement with the statements related to their work performance. Conclusions The data indicates that a clinical trial APN-led telenursing educational intervention results in an overall increase in health literacy, an improvement in health empowerment and health-related quality of life, and a decrease in care needs of oncology clinical trials patients. Patients stated that they received a high quality of care and health professionals indicated high levels of acceptance with APNs. Based on these results, we suggest that the APN role should gain more recognition in the Spanish healthcare system and their professional competencies should be aligned with those of other countries.